Marketing Mix Strategies for Private Schools: Impact on Parental Decision-Making - Bonar Bangun Jeppri Napitupulu; Nelson Silitonga; Rachma Nadhila Sudiyono; Dewiana Novitasari; Sukriyah; Tias Pramono; Jainuri; Masduki Asbari; Multi Nadeak (Yayasan Aya Sophia Indonesia, 2024)
The purpose of this study is to examine and analyze the effect of marketing mix elements which include product, price, place, promotion, people, process, and physical evidence on parents' decisions in choosing a school for their children. This study uses primary data through a survey of 175 parents of active students who live in Tangerang. The collected data were processed and analyzed using SmartPLS software. The results of this study indicate that the six factors of the marketing mix have a positive and significant effect on the decision of parents to choose a school for their children, except for process factors that do not influence parents' decisions in choosing a school for their children An in-depth analysis of the managerial implications for school management and the social implications for society of the results of this study are discussed further in the discussion of this article.